2009
DOI: 10.1093/bioinformatics/btp106
|View full text |Cite
|
Sign up to set email alerts
|

A neural network model for constructing endophenotypes of common complex diseases: an application to male young-onset hypertension microarray data

Abstract: Motivation: Identification of disease-related genes using high-throughput microarray data is more difficult for complex diseases as compared with monogenic ones. We hypothesized that an endophenotype derived from transcriptional data is associated with a set of genes corresponding to a pathway cluster. We assumed that a complex disease is associated with multiple endophenotypes and can be induced by their up/downregulated gene expression patterns. Thus, a neural network model was adopted to simulate the gene–e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 27 publications
1
9
0
1
Order By: Relevance
“…The association of these SNPs with salt sensitivity was replicated in the HyperPATH Cohort at Harvard with a meta-analysis demonstrating significant associations of both SNPs with salt sensitivity (rs7571842 ( P = 1.2×10 −5 ); rs1017783 ( P =1.1× 10 −4 )) [43••]. Our results [43••] are consistent with the association ofrs1017783 and increased blood pressure in African-Americans, Mexican-Americans, Euro-Americans, and Taiwanese [42••, 44••, 45••, 46, 47, 63••, 64]. Another SLC4A5 SNP (rs 10022637) ( P =2.07×10 −6 ) was found to be associated with salt sensitivity in a large cohort of Han Chinese; SLC4A5 rs1017783 was not genotyped [65].…”
Section: Dysregulation Of Nbce2 Activitysupporting
confidence: 80%
See 1 more Smart Citation
“…The association of these SNPs with salt sensitivity was replicated in the HyperPATH Cohort at Harvard with a meta-analysis demonstrating significant associations of both SNPs with salt sensitivity (rs7571842 ( P = 1.2×10 −5 ); rs1017783 ( P =1.1× 10 −4 )) [43••]. Our results [43••] are consistent with the association ofrs1017783 and increased blood pressure in African-Americans, Mexican-Americans, Euro-Americans, and Taiwanese [42••, 44••, 45••, 46, 47, 63••, 64]. Another SLC4A5 SNP (rs 10022637) ( P =2.07×10 −6 ) was found to be associated with salt sensitivity in a large cohort of Han Chinese; SLC4A5 rs1017783 was not genotyped [65].…”
Section: Dysregulation Of Nbce2 Activitysupporting
confidence: 80%
“…Thus, we have demonstrated a functional link between SLC4A5 polymorphisms and renal sodium transport that could make contributions to salt sensitivity [11••]. As previously mentioned, studies from various investigators including ourselves have demonstrated a genetic link between NBCe2 polymorphisms and hypertension [11••, 42••, 43••, 44••, 45••, 46, 47, 63••, 64, 65]. However, these polymorphisms are not in the coding region for SLC4A5 (NBCe2).…”
Section: Dysregulation Of Nbce2 Activitymentioning
confidence: 89%
“…Genetic analysis links single nucleotide polymorphisms (SNPs) in the SLC4A5 gene locus with hypertension and other blood pressure-related traits (61,404,619,915,953,954), including peripheral artery disease (472). One study reports that the contribution of a particular SLC4A5 SNP to elevated systolic blood pressure in African-American women is greater in individuals with dark versus medium skin color (955).…”
Section: Ii) Circulatory System A) Blood Pressure-related Traitsmentioning
confidence: 99%
“…For very complex diseases, such as hypertension, GWAS have revealed very few genes despite a large number of patients that have been studied. It is generally accepted that common complex disease etiologies are heterogeneous in nature [5-8]. In “state of art” GWAS approach, however, inheritance models involving gene-gene interactions and gene-environment interactions [9-13] have not been taken into consideration.…”
Section: Introductionmentioning
confidence: 99%